Studi Analisis Penerapan Model Pembelajaran Kolaboratif Pada Mata Pelajaran Ekonomi - Hilpiana, Lina; Mawarzani , Sapka; Muzakir, Muzakir (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study aims to describe the implementation of collaborative learning and analyze its impact on students’ learning outcomes in economics for Grade X at MA Hubbul Jiron NW Pringgarata. The background of the research stems from the low student engagement in economics learning, which affects academic achievement. The research employed a qualitative method with a descriptive approach. The research subjects included the economics teacher and Grade X students. Data collection techniques involved observation, interviews, documentation, and learning outcome tests. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that collaborative learning improves student participation, strengthens group cooperation, and positively affects learning outcomes. Supporting factors include teacher readiness and student motivation, while inhibiting factors consist of limited time and differences in student ability. This study recommends collaborative learning as an alternative strategy in economics teaching at madrasahs.